Faktor Faktor Implementasi Manajemen Strategis di Lembaga Lembaga Pendidikan Islam - F, Fatmawati; Fathoni, Wildan; Aprianto, Iwan; J, Jamrizal (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The implementation of strategic management in Islamic educational institutions is a crucial process to ensure the effective and sustainable achievement of the institution’s vision, mission, and objectives. This study discusses the stages of strategic management implementation, the influencing factors, and the challenges encountered during its execution. The findings indicate that successful implementation is strongly influenced by the quality of human resources, organizational culture, stakeholder support, and the availability of facilities and infrastructure. Furthermore, external factors such as technological developments, government policies, and socio-cultural dynamics also play a significant role. The main challenges faced include limited resources, resistance to change, and the complexity of the external environment. With a comprehensive understanding of these factors, Islamic educational institutions can design adaptive and responsive strategies to changing times, thereby enhancing quality and competitiveness in a sustainable manner.